Electrode, battery cell, and redox flow battery
By using electrodes of titanium particle sintered substrate and ruthenium oxide catalyst in redox flow batteries, combined with the design of intermediate layer and low iridium palladium, the problems of high cost and insufficient reactivity in the prior art are solved. A low cost, high reactivity and low resistivity battery cells are achieved.
Patent Information
- Application Number
- CN202380041894.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-05-09
- Publication Date
- 2025-01-03
Smart Images

Figure CN119256414A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrode, a battery cell, and a redox flow battery. This application claims priority based on Japanese patent application No. 2022-093332 filed on June 8, 2022. All the contents described in the Japanese patent application are incorporated herein by reference. Background Art
[0002] Patent Documents 1 and 2 disclose electrodes for redox flow batteries. The electrodes have a catalyst supported on a substrate. The catalyst is a metal oxide. The metal oxide that functions as a catalyst contains, for example, a metal element such as ruthenium, iridium, or palladium.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-143002
[0006] Patent Document 2: Japanese Patent Application Publication No. 2019-164882 Summary of the invention
[0007] The electrode disclosed herein is an electrode for a redox flow battery, the electrode comprising a sheet-like substrate and a catalyst supported on the substrate, the substrate being formed of a sintered body in which a plurality of particles containing titanium are bonded to each other, the catalyst comprising a first oxide provided in a manner covering at least a portion of the plurality of particles, the first oxide being an oxide comprising a first element and ruthenium, the first element being at least one selected from the group consisting of tungsten, molybdenum, cerium, neodymium, and vanadium, and each 1 m 2 The content of iridium and the content of palladium contained in the catalyst are each less than 1 g per area.
[0008] The battery cell of the present disclosure is a battery cell of a redox flow battery including a positive electrode and a negative electrode, and at least one of the positive electrode and the negative electrode is the electrode of the present disclosure.
[0009] The redox flow battery of the present disclosure includes the battery cell of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 Schematic diagram showing electrodes according to the embodiment.
[0011] Figure 2 Yes Figure 1 A schematic cross-sectional view showing an enlarged view of the interior of a portion surrounded by a single-dot chain line.
[0012] Figure 3 Yes Figure 2 The enlarged cross-sectional view is shown further enlarged.
[0013] Figure 4 It is a schematic diagram showing the structure of a redox flow battery according to an embodiment. DETAILED DESCRIPTION
[0014] [Problems to be Solved by the Present Disclosure]
[0015] In a redox flow battery, for an electrode loaded with a catalyst, the redox reaction in the electrode is activated, which can improve the battery reactivity with the electrolyte. It is required to reduce the cost of electrodes for redox flow batteries. For an electrode equipped with iridium oxide or palladium oxide as a catalyst, the charging reaction and the discharging reaction in the electrode are promoted. However, the use of iridium oxide or palladium oxide as a catalyst for the electrode will increase the cost of the electrode. It is necessary to minimize the use of iridium and palladium and improve the battery reactivity brought by the catalyst.
[0016] One object of the present disclosure is to provide an electrode having high battery reactivity at low cost. In addition, another object of the present disclosure is to provide a battery cell and a redox flow battery having low battery resistivity.
[0017] [Effects of the present disclosure]
[0018] The electrode disclosed herein has low cost and high battery reactivity. The battery cell and redox flow battery disclosed herein have low battery resistivity.
[0019] [Description of Embodiments of the Present Disclosure]
[0020] First, embodiments of the present disclosure will be described by way of examples.
[0021] (1) An electrode according to an embodiment of the present disclosure is an electrode for a redox flow battery, the electrode comprising a sheet-like substrate and a catalyst supported on the substrate, the substrate being formed of a sintered body in which a plurality of particles containing titanium are bonded to each other, the catalyst comprising a first oxide provided so as to cover at least a portion of the plurality of particles, the first oxide being an oxide comprising a first element and ruthenium, the first element being at least one selected from the group consisting of tungsten, molybdenum, cerium, neodymium, and vanadium, and the electrode having a thickness of 1 m 2 The content of iridium and the content of palladium contained in the catalyst are each less than 1 g per area.
[0022] The electrode disclosed in the present invention has a catalyst carried on a substrate, thereby improving the battery reactivity with the electrolyte compared to the case without a catalyst. The catalyst includes a first oxide, thereby having two functions of an oxidation catalyst and a reduction catalyst. For an electrode having such a catalyst, the charge reaction and the discharge reaction in the electrode are promoted, and thus have high battery reactivity. Therefore, the electrode disclosed in the present invention can reduce the battery resistivity.
[0023] In the electrode of the present disclosure, the content of iridium and the content of palladium contained in the catalyst are small, or the catalyst does not contain iridium and palladium. Therefore, the cost of the electrode of the present disclosure is low.
[0024] (2) In the electrode of (1) above, the first oxide may include at least one element selected from the group consisting of tin, antimony, and titanium.
[0025] According to the configuration of (2) above, the function as a catalyst may be improved or the catalyst may be prevented from falling off from the substrate.
[0026] (3) In the electrode of (1) or (2) above, an intermediate layer may be provided between the particle and the catalyst. The intermediate layer includes a second oxide, the second oxide is an oxide containing at least one element selected from the group consisting of ruthenium, tin, antimony, titanium, tungsten and molybdenum, and the number of types of metal elements contained in the second oxide is less than the number of types of metal elements contained in the first oxide.
[0027] The electrode including the intermediate layer can suppress the catalyst from falling off from the substrate or provide good electrical connection between the substrate and the catalyst.
[0028] (4) In the electrode according to any one of (1) to (3) above, the number of moles of ruthenium in the first oxide may be greater than the total number of moles of the first element.
[0029] According to the configuration of (4) above, the catalyst can have both functions of an oxidation catalyst and a reduction catalyst in a balanced manner.
[0030] (5) In the electrode according to any one of (1) to (4) above, the electrode may have a porosity of 40% by volume or more and 75% by volume or less.
[0031] The electrode having a porosity of 40% by volume or more allows the electrolyte to flow easily in the electrode. The electrode having a porosity of 75% by volume or less has a larger actual volume of the electrode excluding pores, allowing sufficient battery reaction.
[0032] (6) In the electrode of any one of (1) to (5) above, each 1 m 2The content of ruthenium contained in the catalyst is 0.1 g or more and 90.0 g or less per 1 m 2 The total content of the first element contained in the catalyst is 0.1 g or more and 50.0 g or less per area.
[0033] According to the configuration of (6) above, the effect of improving the battery reactivity by the catalyst becomes higher.
[0034] (7) In the electrode according to any one of (1) to (6) above, the electrode may have a tensile strength of 4.0 MPa to 16.0 MPa.
[0035] The tensile strength of the electrode satisfies the above range, so the electrode is not easily deformed or broken. Such an electrode has high operability. In addition, the electrode is appropriately deformed when being installed in the battery cell, and the electrode is not easily damaged.
[0036] (8) In the electrode according to any one of (1) to (7) above, a bending modulus of elasticity of the electrode may be 0.25 GPa or more and 3.0 GPa or less.
[0037] The bending elastic modulus of the electrode satisfies the above range, so that the electrode is not easily deformed or broken. Such an electrode has high operability. In addition, the electrode is appropriately deformed when being installed in the battery cell, and the electrode is not easily damaged.
[0038] (9) A battery cell according to an embodiment of the present disclosure is a battery cell of a redox flow battery including a positive electrode and a negative electrode, and at least one of the positive electrode and the negative electrode is the electrode described in any one of (1) to (8) above.
[0039] The battery cell of the present disclosure has a low battery resistivity and can improve the charging efficiency and discharging efficiency of the redox flow battery.
[0040] (10) In addition, a battery cell of another embodiment of the present disclosure is a battery cell of a redox flow battery having a positive electrode and a negative electrode, one of the positive electrode and the negative electrode is an electrode described in any one of (1) to (8) above, and the other of the positive electrode and the negative electrode has a substrate formed by an aggregate of multiple carbon fibers.
[0041] According to the configuration of (10) above, the battery cell has excellent assembly properties. The electrode having a substrate formed of an aggregate of carbon fibers has higher flexibility than the electrode of the present disclosure having a substrate formed of the sintered body. Therefore, when the positive electrode and the negative electrode are installed in the battery cell, the other electrode is compressed and deformed, and the battery cell is easy to assemble.
[0042] (11) A redox flow battery according to an embodiment of the present disclosure includes the battery cell described in (9) or (10) above.
[0043] The redox flow battery has a low battery resistivity. The redox flow battery includes the battery cell and thus has high charging efficiency and discharging efficiency.
[0044] [Details of the embodiments of the present disclosure]
[0045] Hereinafter, specific examples of electrodes, battery cells, and redox flow batteries according to embodiments of the present disclosure will be described with reference to the accompanying drawings. The same reference numerals in the drawings represent the same or corresponding parts. Hereinafter, redox flow batteries may be referred to as "RF batteries".
[0046] It should be noted that the present invention is not limited to these examples but is shown by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0047] First, refer to Figure 4 The basic structure of RF battery 1 according to the embodiment will be described. Figure 1 to Figure 3 , the electrode 10 of the embodiment is described in detail.
[0048] <RF Battery>
[0049] The RF battery 1 is a storage battery that circulates an electrolyte in a battery cell 100 and performs charging and discharging by utilizing the redox reaction of ions in the electrolyte. In the RF battery 1, the positive electrode electrolyte and the negative electrode electrolyte are electrolytes containing ions whose valences change due to redox as active materials. For example, the electrolyte is a vanadium-based electrolyte or a titanium-manganese-based electrolyte. In a vanadium-based electrolyte, both the positive electrode electrolyte and the negative electrode electrolyte contain vanadium (V) ions. In a titanium-manganese-based electrolyte, the positive electrode electrolyte contains manganese (Mn) ions, and the negative electrode electrolyte contains titanium (Ti) ions.
[0050] The RF battery 1 is typically connected to a power generation unit 8 and a load 9 via an AC / DC converter 7 and a power conversion device 71. The RF battery 1 can be charged with the power generated by the power generation unit 8, or the charged power can be discharged to the load 9. The power generation unit 8 is a power generation device that uses natural energy such as solar power generation and wind power generation, or other general power plants. The RF battery 1 is used, for example, for load balancing, instantaneous voltage drop compensation, emergency power supply, and output smoothing of natural energy power generation.
[0051] RF battery 1 includes battery cell 100, tanks 106 and 107 storing electrolyte, and a circulation path for circulating the electrolyte between tanks 106 and 107 and battery cell 100. Tank 106 stores positive electrode electrolyte. Tank 107 stores negative electrode electrolyte. The configuration of RF battery 1 can utilize a known configuration as appropriate.
[0052] <Battery unit>
[0053] The battery cell 100 includes a positive electrode 104, a negative electrode 105, and a separator 101. The separator 101 is disposed between the positive electrode 104 and the negative electrode 105. The battery cell 100 is separated into a positive electrode cell 102 and a negative electrode cell 103 by the separator 101. The positive electrode 104 is disposed in the positive electrode cell 102. The negative electrode 105 is disposed in the negative electrode cell 103. The positive electrolyte is supplied to the positive electrode cell 102. The negative electrolyte is supplied to the negative electrode cell 103. The positive electrode 104 and the negative electrode 105 are reaction sites where ions contained in the supplied electrolytes undergo a battery reaction. The positive electrode 104 and the negative electrode 105 are composed of, for example, a sheet-like porous body.
[0054] In this example, the circulation flow path of the positive electrode electrolyte is formed by the pipes 108 and 110 connecting the battery cell 100 and the tank 106. The pipe 108 is provided with a pump 112. The positive electrode electrolyte is supplied from the tank 106 to the positive electrode cell 102 via the pipe 108 through the pump 112. The positive electrode electrolyte that passes through the positive electrode cell 102 and is discharged from the positive electrode cell 102 is returned to the tank 106 via the pipe 110. In addition, in this example, the circulation flow path of the negative electrode electrolyte is formed by the pipes 109 and 111 connecting the battery cell 100 and the tank 107. The pipe 109 is provided with a pump 113. The negative electrode electrolyte is supplied from the tank 107 to the negative electrode cell 103 via the pipe 109 through the pump 113. The negative electrode electrolyte that passes through the negative electrode cell 103 and is discharged from the negative electrode cell 103 is returned to the tank 107 via the pipe 111.
[0055] The RF battery 1 may include a single battery cell 100 or a plurality of battery cells 100. Figure 4 As shown, the RF battery 1 of this example includes a battery stack 200 formed by stacking a plurality of battery cells 100. The battery stack 200 is formed by repeatedly stacking a battery frame 120, a positive electrode 104, a separator 101, and a negative electrode 105 in this order. End plates 210 are arranged at both ends of the battery stack 200. The battery stack 200 is integrated by fastening the end plates 210 with a fastening member 230. The structure of the battery stack 200 can appropriately utilize a known structure.
[0056] The battery frame 120 has a bipolar plate 121 and a frame 122. The bipolar plate 121 is arranged between the positive electrode 104 and the negative electrode 105. The frame 122 is arranged around the bipolar plate 121. On the inner side of the frame 122, a recess is formed by the bipolar plate 121 and the frame 122. The recesses are respectively arranged on both sides of the bipolar plate 121. The positive electrode 104 and the negative electrode 105 are respectively accommodated in each recess through the bipolar plate 121.
[0057] like Figure 4 As shown, a battery cell 100 is formed by arranging a positive electrode 104 and a negative electrode 105 between bipolar plates 121 of adjacent battery frames 120 via a separator 101. A sealing member 127, such as an annular one, is arranged between the frame bodies 122 of each battery frame 120. The number of stacked battery cells 100 in the battery stack 200 can be appropriately selected.
[0058] Although not shown, the frame 122 has a supply manifold for supplying each electrolyte and a drain manifold for discharging each electrolyte. Each manifold is provided in a manner penetrating the frame 122, and forms a flow path for each electrolyte by stacking the battery frames 120. Each flow path is connected to each pipe 108, 109, 110, 111, respectively.
[0059] <Electrode>
[0060] like Figure 1 As shown in FIG. 1 , the electrode 10 for the RF battery of the embodiment includes a substrate 20. The substrate 20 is formed of a sintered body. Figure 2 As shown in FIG. 1 , the sintered body is an aggregate of a plurality of particles 21. Figure 3 As shown, the electrode 10 includes a catalyst 30 supported on a substrate 20 . Figure 1 It is an overall view of the electrode 10 . Figure 2 It is schematically indicated Figure 1 An enlarged cross-sectional view of a portion surrounded by a single-dot chain line is shown. Figure 3 Yes Figure 2 The enlarged cross-sectional view is further enlarged and schematically shown. The electrode 10 improves the battery reactivity by supporting the catalyst 30 on the substrate 20. The electrode 10 of this embodiment can improve the battery reactivity at low cost by making the catalyst 30 have a specific oxide.
[0061] <thickness>
[0062] The electrode 10 is a sheet-like porous body. The thickness of the electrode 10 is, for example, not less than 0.1 mm and not more than 5.0 mm. The thickness of the electrode 10 is not less than 0.1 mm, thereby making it easy to ensure the contact area with the electrolyte, that is, the reaction area, and to carry out sufficient battery reaction. The thickness of the electrode 10 is not more than 5.0 mm, thereby making it possible to make the battery cell thinner. The thickness mentioned here refers to the thickness in the natural state when no external force acts on the electrode 10. The thickness of the electrode 10 can also be not less than 0.2 mm and not more than 2.5 mm, or not less than 0.3 mm and not more than 2.0 mm.
[0063] 〈Porosity〉
[0064] The porosity of the electrode 10 is, for example, 40% by volume or more and 75% by volume or less. The porosity of the electrode 10 is 40% by volume or more, which makes it easy for the electrolyte to flow through the electrode 10. The porosity of the electrode 10 is 75% by volume or less, which increases the real volume of the electrode 10 and enables current collection at low resistance. Therefore, if the porosity of the electrode 10 is 75% by volume or less, sufficient battery reaction can be performed. In addition, if the porosity of the electrode 10 is 75% by volume or less, it is easy to ensure the mechanical properties of the electrode 10. The porosity of the electrode 10 can be further 50% by volume or more and 70% by volume or less, particularly 55% by volume or more and 65% by volume or less. The porosity is a value obtained by expressing the value obtained from [1-{W / (ρ×Va)}] as a percentage. ρ is the true density of the material constituting the electrode 10. W is the mass of the electrode 10. Va is the apparent volume of the electrode 10. The apparent volume is the volume including the pores.
[0065] 〈Mechanical properties〉
[0066] It is preferable that the mechanical properties such as strength and rigidity of the electrode 10 are high. The electrode 10 having high mechanical properties is not easily deformed or broken, and thus has high handleability. Examples of mechanical properties include tensile strength, tensile elastic modulus, flexural strength, and flexural elastic modulus.
[0067] The tensile strength of the electrode 10 is, for example, 4.0 MPa or more and 16.0 MPa or less. The tensile strength of the electrode 10 is 4.0 MPa or more, and thus the mechanical properties are high. If the tensile strength of the electrode 10 is 16.0 MPa or less, the electrode 10 is loaded into the battery cell 100 (see Figure 4), the electrode 10 is not easily damaged. The tensile strength of the electrode 10 can further be 5.0 MPa or more and 13.0 MPa or less. The tensile modulus of the electrode 10 is, for example, 1.0 GPa or more and 4.0 GPa or less. The tensile modulus of the electrode 10 is 1.0 GPa or more, so the mechanical properties are high. If the tensile modulus of the electrode 10 is 4.0 GPa or less, the electrode 10 is appropriately deformed when it is loaded into the battery cell 100, and the electrode 10 is not easily damaged. The tensile modulus of the electrode 10 can further be 1.5 GPa or more and 3.5 GPa or less.
[0068] The bending strength of the electrode 10 is, for example, 3.0 MPa or more and 30.0 MPa or less. The bending strength of the electrode 10 is 3.0 MPa or more, so that the mechanical properties are high. If the bending strength of the electrode 10 is 30.0 MPa or less, the electrode 10 is appropriately deformed when it is loaded into the battery cell 100, and the electrode 10 is not easily damaged. The bending strength of the electrode 10 may further be 10.0 MPa or more and 20.0 MPa or less. The bending modulus of the electrode 10 is, for example, 0.25 GPa or more and 3.0 GPa or less. By making the bending modulus of the electrode 10 be 0.25 GPa or more, the mechanical properties are high. If the bending modulus of the electrode 10 is 3.0 GPa or less, the electrode 10 is appropriately deformed when it is loaded into the battery cell 100, and the electrode 10 is not easily damaged. The bending modulus of the electrode 10 may further be 1.0 GPa or more and 2.5 GPa or less.
[0069] (Base material)
[0070] The substrate 20 is a porous body that serves as the skeleton of the electrode 10. The substrate 20 has the conductivity required for the electrode 10. In this embodiment, the substrate 20 is composed of a sintered body of titanium (Ti). Figure 2 As shown, the sintered body of Ti constituting the substrate 20 is composed of a plurality of particles 21 containing Ti bonded to each other. The sintered body has a three-dimensional network skeleton structure due to the plurality of particles 21 bonded to each other. There are pores between the particles 21. The particles 21 containing Ti are composed of pure Ti or Ti alloy. Pure Ti contains more than 99 mass % of Ti, and the remainder is composed of inevitable impurities. Ti alloys include α-type Ti alloys, α+β-type Ti alloys, β-type Ti alloys, corrosion-resistant Ti alloys, etc.
[0071] <thickness>
[0072] The substrate 20 is in a sheet shape and has a thickness substantially equal to the thickness of the electrode 10 described above.
[0073] 〈Porosity〉
[0074] The porosity of the substrate 20 is substantially equal to the porosity of the electrode 10 described above. Figure 3 As shown, the catalyst 30 is supported on the substrate 20, so strictly speaking, the porosity of the substrate 20 is slightly larger than the porosity of the electrode 10. The amount of the catalyst 30 supported on the substrate 20 is small, so the difference in porosity caused by the presence or absence of the catalyst 30 can be ignored.
[0075] Each 1m of electrode 10 2 The mass of the substrate 20 per unit area is, for example, 300 g or more and 3000 g or less. Here, the area of the electrode 10 refers to the area when the electrode 10 is viewed from above, that is, the projection area onto the electrode 10. The mass of the substrate 20 per unit area is 300 g / m 2 As a result, the actual volume of the substrate 20 excluding the pores becomes larger, making it easier to ensure conductivity and mechanical properties. The mass of the substrate 20 per unit area is 3000 g / m 2 The mass of the substrate 20 per unit area can be further 400 g / m 2 Above and 2000g / m 2 The true volume of the substrate 20 is a value obtained by dividing the mass of the substrate 20 by the density of the material constituting the substrate 20 .
[0076] 〈Average particle size〉
[0077] The average particle size of the particles 21 is, for example, not less than 3 μm and not more than 500 μm. The average particle size of the particles 21 is not less than 3 μm, so that the particles 21 are easy to handle. The average particle size of the particles 21 is not more than 500 μm, so that the surface area of the sintered body constituting the substrate 20 can be increased, and the reaction area can be easily ensured. The average particle size of the particles 21 can further be not less than 4 μm and not more than 300 μm, or not less than 5 μm and not more than 50 μm. It should be noted that when the volume of the particles 21 is set to Vp, the particle size of the particles 21 is [2×(3Vp / 4π) 1 / 3 ]. The average value of these values becomes the average particle size of the particles 21.
[0078] The average particle size of the particles 21 can be calculated as follows. Observe the cross section of the substrate 20 using a scanning electron microscope (SEM). The size of the observation field is set to include 50 or more particles 21 in the observation field. Measure the particle size of all particles 21 in the observation field. The particle size of the particle 21 is set to the diameter of a circle having an area equal to the cross-sectional area of the particle 21. The cross-sectional area of the particle 21 can be calculated by image processing. The average value of the measured particle sizes of the particles 21 is regarded as the average particle size of the particles 21.
[0079] (catalyst)
[0080] The catalyst 30 is supported on the substrate 20. Figure 3As shown in FIG. 1 , the catalyst 30 is formed in a layer on the surface of the particle 21 so as to cover the particle 21 constituting the substrate 20. Figure 2 At least a part of the multiple particles 21 shown in the figure may be sufficient. The catalyst 30 may be provided on particles of more than 80% of all the particles 21, or may be provided on all the particles 21. This ratio is the ratio of the number of particles 21 having the catalyst 30 to the number of all the particles. In the present embodiment, the catalyst 30 is provided on substantially all the particles 21. The catalyst 30 may be in direct contact with the surface of the particle 21, or may be provided on the surface of the particle 21 via the intermediate layer 40. The catalyst 30 has the function of activating the redox reaction in the electrode 10 and improving the battery reactivity with the electrolyte.
[0081] 〈Material〉
[0082] Catalyst 30 has a first oxide. The first oxide is composed of an oxide containing ruthenium (Ru) and a first element. The first element is at least one selected from the group consisting of tungsten (W), molybdenum (Mo), cerium (Ce), neodymium (Nd) and vanadium (V). The first oxide is, for example, a composite oxide containing Ru and W, a composite oxide containing Ru and Mo, a composite oxide containing Ru and Ce, a composite oxide containing Ru and Nd, or a composite oxide containing Ru and V. The first oxide may contain a variety of first elements. The inventors and others conducted in-depth research and found that the composite oxide of Ru and the first element has excellent function as a catalyst 30. Such a composite oxide has both the functions of an oxidation catalyst and a reduction catalyst. Catalyst 30 has both the functions of an oxidation catalyst and a reduction catalyst, thereby promoting the charge reaction and the discharge reaction in the electrode 10. Generally speaking, an oxide containing Ru but not containing the first element has the function of an oxidation catalyst, but the function as a reduction catalyst is poor. It is considered that by compounding Ru with the first element, the function as a reduction catalyst will be improved.
[0083] The first oxide may further include at least one element selected from the group consisting of tin (Sn), antimony (Sb) and titanium (Ti). The first oxide may include at least one element of Sn, Sb and Ti, thereby sometimes being able to improve the function as a catalyst or suppress the catalyst from falling off from the substrate.
[0084] 〈Molar Ratio of Ru〉
[0085] It may be that the molar number of Ru in the first oxide is more than the total molar number of the first element. That is, the molar ratio of Ru to the total of the first element may exceed 1. The molar ratio of Ru to the total of the first element is large, so that the two functions of oxidation catalyst and reduction catalyst can be balanced. The molar ratio of Ru to the total of the first element may be, for example, 5 or more and 40 or less, and further may be 10 or more and 25 or less. When the total of all metal elements contained in the first oxide is set to 100 mol%, the content of Ru is, for example, 50 mol% or more and 80 mol% or less, and further 55 mol% or more and 75 mol% or less. The total content of the first element is, for example, 2 mol% or more and 40 mol% or less, and further 2 mol% or more and 10 mol% or less.
[0086] 〈Ru content〉
[0087] Each 1m of electrode 10 2 The content of Ru contained in the catalyst 30 per unit area can be 0.1 g or more and 90.0 g or less, and the total content of the first element contained in the catalyst 30 can be 0.1 g or more and 50.0 g or less. The content of Ru per unit area and the total content of the first element satisfy the above ranges, respectively, thereby increasing the effect of improving the battery reactivity brought about by the catalyst 30. If the content of Ru and the total content of the first element satisfy the above ranges, respectively, the cost increase of the electrode 10 can be suppressed. The content of Ru per unit area can further be 0.1 g / m 2 Above and 40.0g / m 2 Below, can also be 0.1g / m 2 Above and 30.0g / m 2 The total content of the first element per unit area may further be 0.1 g / m 2 Above and 10.0g / m 2 the following.
[0088] Each 1m of electrode 10 2 The mass of the catalyst 30 per unit area may be 1 g or more and 100 g or less. The mass of the catalyst 30 per unit area is 1 g / m 2 The mass of the catalyst 30 per unit area is 100 g / m 2 The content of the catalyst 30 is small, and the cost of the electrode 10 is reduced. The mass of the catalyst 30 per unit area can be further 2 g / m 2 Above and 80g / m 2 Below, 2g / m 2 Above and 60g / m 2 the following.
[0089] The catalyst 30 may also contain an oxide other than the first oxide described above, and a metal element such as gold (Au) or platinum (Pt). The oxide other than the first oxide is, for example, an oxide containing Sn, Sb, Ti, etc. alone. The total content of Au and Pt per unit area may be 1 g / m 2 Au and Pt are expensive metals. The lower the content of Au and Pt, the lower the cost. The content of Au and Pt per unit area can be 0.5 g / m 2 Below, further can be 0.1g / m 2 In other words, Au and Pt may not be contained in the electrode 10. The proportion of the first oxide contained in the catalyst 30 may be 60% by mass or more, and further may be 80% by mass or more. The proportion of the first oxide may also be 100% by mass. In other words, the catalyst 30 may be composed only of the first oxide.
[0090] 〈Ir content, Pd content〉
[0091] Each 1m of electrode 10 2 The content of iridium (Ir) and the content of palladium (Pd) contained in the catalyst 30 are each less than 1 g. The content of Ir and the content of Pd per unit area are 1 g / m 2 The cost of the electrode 10 is reduced. Preferably, the total content of Ir and Pd per unit area is 1 g / m 2 The lower the content of Ir and Pd per unit area, the higher the cost reduction effect. The content of Ir and Pd per unit area can be 0.5 g / m 2 Below, further can be 0.1g / m 2 In particular, the content of Pd may be zero. That is, the electrode 10 may not contain Ir or Pd.
[0092] (Middle layer)
[0093] like Figure 3 As shown, the electrode 10 may include an intermediate layer 40 between the particles 21 constituting the substrate 20 and the catalyst 30. The intermediate layer 40 is provided so as to cover the particles 21. The intermediate layer 40 is in direct contact with the surface of the particles 21. The catalyst 30 is supported on the particles 21 via the intermediate layer 40. The intermediate layer 40 has the function of inhibiting the catalyst 30 from falling off from the particles 21 and electrically connecting the particles 21 and the catalyst 30.
[0094] 〈Material〉
[0095] The intermediate layer 40 includes a second oxide. The second oxide is composed of an oxide containing at least one element selected from the group consisting of Ru, Sn, Sb, Ti, W, and Mo. The second oxide containing such a specific metal element can function as the intermediate layer 40.
[0096] The metal element contained in the second oxide may include one or more elements of the same kind as the metal element contained in the first oxide constituting the catalyst 30. The second oxide and the first oxide contain the same metal element, and thus the same metal elements are bonded to each other at the interface between the intermediate layer 40 and the catalyst 30. As a result, the adhesion between the intermediate layer 40 and the catalyst 30 is improved, and the conductivity between the intermediate layer 40 and the catalyst 30 is improved. In addition, at the interface between the particle 21 and the intermediate layer 40, oxygen (O) in the second oxide diffuses and bonds to Ti constituting the particle 21. As a result, the adhesion between the particle 21 and the intermediate layer 40 is improved, and the conductivity between the particle 21 and the intermediate layer 40 is improved. Therefore, the second oxide and the first oxide contain the same metal element, and thus the catalyst 30 is not easy to fall off from the particle 21, and the particle 21 and the catalyst 30 can be well electrically connected. The second oxide may contain at least one of Ru, Sn and Ti in the above-mentioned group of elements, and may particularly contain Ru. In the case where the second oxide contains Ru, since the first oxide contains Ru, the effect of improving the adhesion between the intermediate layer 40 and the catalyst 30 is high. In addition, when the second oxide includes Sn, Sn easily diffuses into Ti constituting the particle 21, so the adhesion between the particle 21 and the intermediate layer 40 is improved. When the second oxide includes Ti, Ti in the second oxide is combined with Ti constituting the particle 21, so the adhesion between the particle 21 and the intermediate layer 40 is improved.
[0097] The intermediate layer 40 electrically connects the particle 21 and the catalyst 30, so the conductivity of the intermediate layer 40 is required to be higher than that of the catalyst 30. That is, the resistivity of the intermediate layer 40 can be less than the resistivity of the catalyst 30. In order to improve the conductivity of the intermediate layer 40, the number of types of metal elements contained in the second oxide can be less than the number of types of metal elements contained in the first oxide constituting the catalyst 30. The fewer the number of types of metal elements contained in the second oxide, the higher the conductivity of the second oxide. Therefore, the resistivity of the intermediate layer 40 is smaller. Furthermore, if the metal element contained in the second oxide is a metal element with high conductivity in the above-mentioned group of elements, the resistivity of the intermediate layer 40 becomes smaller. The smaller the resistivity of the intermediate layer 40, the lower the resistance of the particle 21 and the catalyst 30 can be connected with low resistance. The number of types of metal elements contained in the second oxide can be less than 3, and can also be less than 2. The number of types of metal elements contained in the second oxide can also be 1.
[0098] The thickness of the intermediate layer 40 may be thinner than that of the catalyst 30. 2 The mass of the intermediate layer 40 per unit area may be greater than 1 g and less than 40 g. The mass of the intermediate layer 40 per unit area is 1 g / m 2 As described above, the function of the intermediate layer 40 can be fully exerted. The mass of the intermediate layer 40 per unit area is 40 g / m 2 The content of the intermediate layer 40 is small, and the cost of the electrode 10 is reduced. The mass of the intermediate layer 40 per unit area can be further 1.5 g / m 2 Above and 35g / m 2 the following.
[0099] It should be noted that the inventors have conducted in-depth research and found that by providing the catalyst 30 on the intermediate layer 40, even if the catalyst 30 is a small amount, the effect of improving the battery reactivity can be fully exerted. Therefore, when the electrode 10 has the intermediate layer 40, the content of the catalyst 30 is less than that of the case where the intermediate layer 40 is not provided. For example, the mass of the catalyst 30 per unit area can be 60 g / m 2 Below, further can be 50g / m 2 the following.
[0100] The electrode 10 for the RF battery of the present embodiment can be used for both the positive electrode 104 and the negative electrode 105 of the RF battery 1. The electrode 10 is particularly preferably used for the positive electrode 104. When the electrode 10 is used for the negative electrode 105, the sintered body of Ti constituting the substrate 20 may be degraded due to contact with the negative electrode electrolyte. In addition, in the battery cell 100, when one of the positive electrode 104 and the negative electrode 105 is the electrode 10 of the present embodiment, the other may also be an electrode having a substrate formed by an aggregate of multiple carbon fibers. The aggregate of carbon fibers is composed of multiple carbon fibers entangled with each other. The aggregate of carbon fibers is typically carbon felt. The electrode having a substrate formed by an aggregate of carbon fibers has higher flexibility than the electrode 10 having a substrate 20 formed by a sintered body of Ti. Therefore, when the positive electrode 104 and the negative electrode 105 are loaded into the battery cell 100, the battery cell 100 is easily assembled by compressing and deforming the electrode having a substrate formed by an aggregate of carbon fibers.
[0101] <Electrode Manufacturing Method>
[0102] The electrode 10 can be manufactured as follows. A substrate 20, a first solution, and a second solution are prepared. The first solution contains a metal element constituting a first oxide that becomes a catalyst 30. The second solution contains a metal element constituting a second oxide that becomes an intermediate layer 40. The second solution is applied to the substrate 20 and heat-treated, thereby forming the intermediate layer 40 on the substrate 20. After the intermediate layer 40 is formed, the first solution is applied to the substrate 20 and heat-treated, thereby forming the catalyst 30 on the substrate 20. The manufacturing method of the electrode 10 is described in detail below.
[0103] (Preparation of substrate)
[0104] A sintered body of Ti is prepared as the substrate 20. The size and shape of the sintered body can be appropriately selected so as to obtain the size and shape of the desired electrode 10. The substrate 20 can be made as follows. Ti powder is filled into a molding die to make a molded body. The Ti powder is composed of particles 21 containing Ti. By sintering the molded body, a substrate 20 formed by a sintered body formed by a plurality of particles 21 bonded to each other is made. The sintering temperature during sintering is, for example, 800°C or more and 1500°C or less. The holding time at the sintering temperature is, for example, 30 minutes or more and 3 hours or less. There is a tendency that the higher the sintering temperature, the higher the strength of the sintered body.
[0105] (Solution Preparation)
[0106] The first solution is a solution containing a raw material of a metal element constituting the first oxide and an organic solvent. The second solution is a solution containing a raw material of a metal element constituting the second oxide and an organic solvent. The raw material of the metal element includes an organic compound, chloride, metal alkoxide, acetate, etc.
[0107] Examples of the raw material of Ru include ruthenium (III) chloride hydrate, ruthenium (III) nitrate, ruthenium (IV) oxide hydrate, ruthenium (III) acetate, ruthenium (III) tris(acetylacetonate), and hexaammineruthenium (III) chloride.
[0108] The raw material of W includes, for example, tungsten (VI) ethoxide, tungsten (VI) phenoxide, bis(cyclopentadienyl)tungsten (IV) dichloride, tungsten hexacarbonyl, and tungsten chloride.
[0109] Examples of the raw material of Mo include molybdenum (V) ethoxide, molybdenum (IV) dioxide bis(acetylacetonate), molybdenum (II) acetate, molybdenum (II) acetate dimer, molybdenum carbonyl, molybdenum 2-ethylhexanoate, and molybdenum (V) chloride.
[0110] Examples of the raw material of Ce include cerium (III) nitrate, cerium (III) chloride, cerium (III) chloride heptahydrate, cerium (IV) isopropoxide, cerium (IV) methoxyethoxide, cerium (III) tert-butoxide, and cerium (III) 2-ethylhexanoate.
[0111] Examples of the raw material of Nd include neodymium (III) isopropoxide, neodymium (III) acetylacetonate, neodymium (III) trifluoroacetylacetonate, neodymium nitrate hexahydrate, neodymium acetate monohydrate, neodymium chloride monohydrate, neodymium chloride hexahydrate, neodymium fluoride, and neodymium (III) 2-ethylhexanoate.
[0112] The raw materials of V include, for example, vanadium (III) acetylacetonate, bis(acetylacetonate) vanadium (IV) oxide, vanadium (V) trichloride, bis(2,4-pentanedionato) vanadium (IV) oxide, vanadium (V) trifluoride, vanadium (III) chloride, triisopropoxy vanadium (V) oxide, vanadium (III) fluoride, vanadium (III) bromide, vanadium (V) trichloride, vanadium oxalate n-hydrate, bis(cyclopentadienyl) vanadium dichloride, tetracarbonylcyclopentadienyl vanadium, and vanadium 2-ethylhexanoate.
[0113] The raw materials of Sn include, for example, tin tetrachloride, tin (IV) chloride pentahydrate, tin (II) chloride, tin (II) chloride dihydrate, bis(2-ethylhexanoate)tin (II), bis(neodecanoate)tin (II), n-butyltin trichloride (IV), dibutyltin bisacetylacetonate, di-n-butyltin di-n-butoxide (IV), tin (IV) n-butoxide, tin (IV) tert-butoxide, tetramethyltin, tin (II) acetate, and tin (IV) acetate.
[0114] Examples of the raw material of Sb include triisopropoxide antimony, tri-n-propoxide antimony, tri-n-butoxide antimony, triisobutoxide antimony, trimethoxide antimony, antimony (III) acetate, antimony trichloride, antimony pentachloride, antimony (III) methoxide, antimony (III) ethoxide, and antimony (III) butoxide.
[0115] The raw materials of Ti include, for example, titanium tetrachloride, titanium (IV) ethoxide, titanium (IV) n-butoxide, titanium (IV) tert-butoxide, titanium (IV) isopropoxide, titanium (IV) n-propoxide, titanium (IV) isotripropoxide monochloro, titanium (IV) methoxide, titanium (IV) n-butoxide (bis-2,4-neodecanoate), titanium (IV) dichloroethoxide, titanium (IV) isopropoxide (bis-2,4-pentanedionate), titanium (IV) 2-ethylhexanoate, titanium (IV) cresol, and titanium (IV) n-stearyl alcohol.
[0116] The organic solvent is, for example, trifluoroethanol, pentafluoropropanol, 2,2,3,3,4,4,4-heptafluoro-1-butanol, methanol, ethanol, propanol, isopropanol, butanol, pentanol, hexanol, 3-methoxy-3-methyl-1-butanol, acetonitrile, propylene carbonate, and ethylene carbonate. The organic solvent may contain 70% by mass or more and 95% by mass or less relative to the whole solution. In addition, the solution may contain a stabilizer as needed. The stabilizer is, for example, acetylacetone. The stabilizer may contain 1% by mass or more and 10% by mass or less relative to the whole solution. The first solution and the second solution are prepared by stirring the raw material containing the above-mentioned metal element, the organic solvent, and the liquid containing the stabilizer in an inert gas atmosphere. The inert gas is, for example, nitrogen and argon. The raw material of the metal element is prepared in such a way that the concentration of the metal element becomes the desired ratio. The stirring time is, for example, about 1 hour or more and about 5 hours or less.
[0117] (Coating and heat treatment)
[0118] The solution is applied to the substrate 20 formed by the sintered body, so that the solution penetrates into the inside of the substrate 20. The solution is applied in a manner that covers the particles 21 constituting the substrate 20. The solution application method includes, for example, a brush coating method, a spraying method, a dipping method, a flow coating method, a roller coating method, and a dipping method. The substrate 20 coated with the solution is dried. The substrate 20 coated with the solution is subjected to a heat treatment. The heat treatment includes a first heat treatment, a second heat treatment, and a final heat treatment. The temperature of the heat treatment is, for example, above 300° C. and below 600° C. The time of the heat treatment is, for example, above 10 minutes and below 5 hours. The atmosphere of the heat treatment is an atmosphere containing an oxidizing gas. The oxidizing gas is, for example, air. Through the heat treatment, the metal elements contained in the solution are oxidized to become oxides. When the first solution is used, a first oxide is formed. When the second solution is used, a second oxide is formed.
[0119] When manufacturing the electrode 10 having the catalyst 30 and the intermediate layer 40, the step of forming the catalyst 30 is performed after the step of forming the intermediate layer 40. In the step of forming the intermediate layer 40, the second heat treatment is performed after the second solution is applied to the substrate 20. Through this step, the intermediate layer 40 having the second oxide is formed, and the intermediate layer 40 is supported on the substrate 20. Specifically, a series of operations of [application of the second solution] → [drying] → [second heat treatment] are repeated until the desired amount of the intermediate layer 40 is supported on the substrate 20. The second heat treatment makes it easy to produce a phenomenon that the constituent elements in the second oxide diffuse from the intermediate layer 40 to the particles 21. The conditions of the second heat treatment in this operation are, for example, 300° C. or higher and 500° C. or lower × 10 minutes or higher and 2 hours or lower. The more times the above operation is repeated, the thicker the intermediate layer 40 is, and the more the weight of the intermediate layer 40 increases. The number of times this operation is repeated is appropriately selected so that the mass of the intermediate layer 40 per unit area of the electrode 10 becomes the desired mass. In the step of forming the intermediate layer 40 , the above operation may be repeated, for example, once or more and five times or less, and further may be repeated once or more and four times or less.
[0120] In the process of forming the catalyst 30, the first heat treatment is performed after the first solution is applied to the substrate 20 on which the intermediate layer 40 is formed. Through this process, the catalyst 30 having the first oxide is formed on the intermediate layer 40, and the catalyst 30 is supported on the substrate 20 via the intermediate layer 40. Specifically, a series of operations of [coating of the first solution] → [drying] → [first heat treatment] are repeated until the desired amount of the catalyst 30 is supported on the substrate 20. Through the first heat treatment, it is easy to produce a phenomenon in which the constituent elements in the second oxide and the constituent elements in the first oxide diffuse mutually between the intermediate layer 40 and the catalyst 30, and the same metal elements are combined with each other. The conditions of the first heat treatment in this operation are, for example, 300°C or more and 500°C or less × 10 minutes or more and 2 hours or less. The more times the above operation is repeated, the thicker the catalyst 30 is, and the more the weight of the catalyst 30 increases. The number of times this operation is repeated is appropriately selected so that the mass of the catalyst 30 per unit area of the electrode 10 becomes the desired mass. In the step of forming the catalyst 30 , the above operation may be repeated, for example, once or more and ten times or less, and further may be repeated two or more and eight times or less.
[0121] In the above-mentioned steps of forming the intermediate layer 40 and forming the catalyst 30, if the number of times the above-mentioned operation is repeated increases, the number of heat treatments increases, and the mechanical properties of the substrate 20 may be reduced due to the heat treatment. From the viewpoint of maintaining the mechanical properties of the substrate 20, the total number of heat treatments in the two steps may be, for example, 10 times or less, further 8 times or less, and particularly 6 times or less.
[0122] After the step of forming the catalyst 30, the substrate 20 formed with the catalyst 30 and the intermediate layer 40 may be subjected to a final heat treatment. The conditions of the final heat treatment are, for example, 400°C or higher and 600°C or lower for 1 hour or higher and 5 hours or lower. The temperature and time of the final heat treatment may be higher than the temperature in the first heat treatment and the second heat treatment, and longer than the time in the first heat treatment and the second heat treatment. Thus, the metal element in the first oxide and the metal element in the second oxide are easily fully oxidized.
[0123] [Test Example 1]
[0124] An electrode including a substrate, an intermediate layer, and a catalyst was produced, and the electrode was evaluated.
[0125] The prepared substrate is a sintered body of Ti. The sintered body of Ti is made as follows. Ti powder is filled into a molding die to make a molded body. The particle size of the Ti particles constituting the Ti powder is 45 μm or less. As for the size of the molded body, the area is 30 mm×30 mm and the thickness is 0.5 mm. The molded body is sintered in an argon atmosphere to make a sintered body of Ti. The porosity of the substrate formed by the sintered body of Ti is about 60% by volume. The mass of the substrate per unit area is about 1300 g / m 2 . In this example, the sintering temperature is changed to produce three types of sintered bodies A to C. Sintered body A is a sintered body sintered at 1000°C for 1 hour. Sintered body B is a sintered body sintered at 950°C for 2 hours. Sintered body C is a sintered body sintered at 900°C for 3 hours. Among the samples shown in Tables 1 and 2, the substrate of sample No. 12 is sintered body B. The substrate of sample No. 13 is sintered body C. The substrates of samples other than samples No. 12 and No. 13 are sintered body A.
[0126] The solution was applied to the substrate and then heat treated to form the intermediate layer and catalyst shown in Tables 1 and 2. The [Mass (g / m 2 The column [Mass (g / m 2)] column shows the mass of the catalyst per unit area of the electrode. As solutions, a first solution for forming a catalyst and a second solution for forming an intermediate layer are prepared. The first solution is a solution in which the raw materials of the metal elements constituting the first oxide shown in Tables 1 and 2 are mixed with an organic solvent. The second solution is a solution in which the raw materials of the metal elements constituting the second oxide shown in Tables 1 and 2 are mixed with an organic solvent. The organic solvent uses butanol to which 1% by mass of acetylacetone is added as a stabilizer. As raw materials of metal elements, dibutyltin diacetylacetonate, ruthenium (IV) oxide hydrate, ethanol antimony (III), ethanol tungsten (VI), molybdenum chloride, triisopropoxycerium, neodymium (III) chloride hexahydrate, vanadium (III) chloride, iridium trichloride, and palladium dichloride are prepared. Each solution is prepared by stirring the raw materials of the metal elements in an organic solvent added with a stabilizer for 5 hours in a nitrogen atmosphere.
[0127] As the first solution, a solution in which a raw material of a metal element is selected so that the metal element in the first solution becomes a metal element constituting the first oxide shown in Table 1 and Table 2 is prepared. The raw materials of the metal element are prepared so that the molar concentration of the metal element in the first solution becomes the molar ratio shown in Table 1 and Table 2. In addition, the first solution is prepared so that the total amount of the metal element in the first solution becomes 10% by mass. For example, in the case of the catalyst of sample No. 1 shown in Table 1, dibutyltin diacetylacetonate, ruthenium (IV) oxide hydrate, and tungsten (VI) ethoxide are used as the raw materials of the metal element constituting the first oxide. The raw materials of these metal elements are prepared so that the molar concentration of each metal element in the first solution becomes the molar ratio shown in Table 1. In the "catalyst" item of Table 1 and Table 2, for example, when [Sn / Ru / W] is recorded in the "first oxide" column and [30:65:5] is recorded in the "molar ratio" column, it means that the first oxide contains Sn, Ru, and W, and the molar ratio of Sn to Ru to W is 30:65:5. It should be noted that a very small amount of antimony (III) ethoxide was mixed in the first solution. Although not described in Tables 1 and 2, the first oxide of each sample contained less than 3 mol % of Sb.
[0128] As the second solution, a solution of a raw material of a metal element is prepared in such a way that the metal element in the second solution becomes a metal element constituting the second oxide shown in Table 1 and Table 2. The second solution is prepared in such a way that the total amount of the metal element in the second solution becomes 5% by mass. For example, in the case of the intermediate layer of sample No. 1 shown in Table 1, ruthenium (IV) oxide hydrate is used as a raw material of the metal element constituting the second oxide. In the "intermediate layer" item of Table 1 and Table 2, for example, when [Ru] is recorded in the "second oxide" column, it means that the second oxide contains Ru.
[0129] First, in order to form an intermediate layer, the second solution is applied to the substrate by a brush coating method. After the second solution is applied, the substrate is dried. Thereafter, the substrate coated with the second solution is subjected to a second heat treatment. Specifically, [application of the second solution] → [drying] → [second heat treatment] are repeated until the mass of the intermediate layer per unit area becomes the mass shown in Tables 1 and 2. The conditions of the second heat treatment are 400°C × 10 minutes.
[0130] Next, in order to form a catalyst, the first solution is applied to the substrate on which the intermediate layer is formed by a brush coating method. After the first solution is applied, the substrate is dried. Thereafter, the substrate coated with the first solution is subjected to a first heat treatment. Specifically, [application of the first solution] → [drying] → [first heat treatment] are repeated until the mass of the catalyst per unit area becomes the mass shown in Tables 1 and 2. The conditions for the first heat treatment are 400°C × 10 minutes.
[0131] Finally, the substrate with the intermediate layer and the catalyst formed thereon was subjected to a final heat treatment at 500°C for 1 hour. As described above, electrodes of samples No. 1 to No. 17 shown in Table 1 and electrodes of samples No. 101 to No. 118 shown in Table 2 were manufactured. The electrode of sample No. 109 had no intermediate layer formed thereon.
[0132] (Composition Analysis)
[0133] For each sample obtained, the composition analysis of the cross section of the electrode was performed using SEM and EDX. In all samples except sample No. 109, as shown in Tables 1 and 2, the metal elements contained in the second oxide constituting the intermediate layer were confirmed. In addition, in all samples, as shown in Tables 1 and 2, the metal elements contained in the first oxide constituting the catalyst were confirmed. Furthermore, the crystal structure was analyzed using an X-ray diffraction device (XRD), and the elemental composition was determined using an X-ray microanalyzer (EPMA), thereby investigating the existence state of the intermediate layer and the catalyst, and the result confirmed that it was an oxide containing metal elements. It can be seen that the intermediate layer is composed of the second oxide shown in Tables 1 and 2. It can be seen that the catalyst is composed of the first oxide shown in Tables 1 and 2.
[0134] Based on the results of the composition analysis of each sample, the contents of Ru and the first element per unit area of the electrode (g / m 2 In addition, the content of each element of Ir and Pd per unit area of the electrode was calculated (g / m 2 ). The results are shown in Tables 1 and 2. It should be noted that the content of the first element is represented by the total content of W, Mo, Ce, Nd and V.
[0135] (Battery resistivity)
[0136] The electrodes of each sample were used as the positive electrode of the RF battery to produce a single battery cell. Carbon felt was used as the negative electrode. The area of the positive electrode and the negative electrode were 9 cm 2 The electrolyte used was a sulfuric acid aqueous solution containing 1M Ti and 1M Mn dissolved therein. The battery cell was used for charge and discharge tests to investigate the battery resistivity. The test conditions were a current density of 140 mA / cm 2 The battery is charged and discharged at a constant current. In this test, if the upper limit voltage of 1.6V is reached, the charge is switched to the discharge, and if the lower limit voltage of 0.9V is reached, the discharge is switched to the charge, and 4 cycles of charge and discharge are performed. The battery resistivity is calculated as follows. The difference between the average voltage during charging and the average voltage during discharging in each cycle from 2 to 4 cycles is measured. This difference is taken as the average voltage difference. The [average voltage difference / (average current×2)×electrode area] in each cycle is taken as the battery resistivity in that cycle (Ωcm 2 ). The average value of the resistivity of each battery from 2 cycles to 4 cycles is taken as the battery resistivity. The average voltage during charging is the battery voltage at which the charging capacity is 1 / 2 in the charging curve obtained by the charge and discharge test. The average voltage during discharging is the battery voltage at which the charging capacity is 1 / 2 in the discharge curve obtained by the charge and discharge test. The charging curve represents the relationship between the voltage and capacity during charging. The discharge curve represents the relationship between the voltage and capacity during discharge. The charging curve and the discharge curve are curves in which the horizontal axis uses the battery capacity (Ah) and the vertical axis uses the battery voltage (V) and the transition of the charging and discharging state at the same current is graphed. The average current is the average value of the current during charging and discharging. In the charge and discharge test, charging and discharging are performed in a constant current mode, so the current during charging and discharging is constant. The battery resistivity of each sample is shown in Tables 1 and 2.
[0137] (Mechanical properties)
[0138] The mechanical properties of each sample were evaluated. Here, as the mechanical properties of the electrode, the tensile strength, tensile elastic modulus, flexural strength, and flexural elastic modulus were measured.
[0139] The tensile strength and tensile modulus are measured using a tensile testing machine. The shape of the test piece is a rectangle with a length of about 150 mm and a width of about 5 mm. The test piece is made as follows. A sintered body of Ti with a larger area than the test piece and a thickness of 5 mm is made. The sintered body of Ti is used for a substrate, and an intermediate layer and a catalyst are formed on the substrate by the above-mentioned formation method. The electrodes of each obtained sample are processed into the size of the above-mentioned test piece. The tensile testing machine used is TENSILON UCT-30T manufactured by ORIENTEC Co., Ltd. The conditions of the tensile test are as follows.
[0140] Strain measurement: Crosshead travel method
[0141] Distance between fixtures: 10mm
[0142] Test speed: 1mm / min
[0143] Test temperature: 23℃±2℃
[0144] The tensile modulus was calculated from the maximum gradient value based on the 0.1% strain interval. For the tensile strength and tensile modulus, three tensile tests were performed and the average values were used. The tensile strength and tensile modulus of each sample are shown in Tables 1 and 2.
[0145] The bending strength and bending modulus are measured by a three-point bending test. The three-point bending test is performed in accordance with JIS Z 2248: 2014. As for the size of the test piece, the length is about 150 mm, the width is about 30 mm, and the thickness is about 0.5 mm. The test piece is made as follows. A sintered body of Ti having an area larger than the test piece and a thickness of 0.5 mm is made. The sintered body of Ti is used for a substrate, and an intermediate layer and a catalyst are formed on the substrate by the above-mentioned formation method. The electrodes of each obtained sample are processed into the size of the above-mentioned test piece. The bending test uses a composite material testing machine model 5966 manufactured by Instron. The maximum load of the testing machine is 10 kN. The conditions of the bending test are described as follows.
[0146] Test speed: 2mm / min
[0147] Distance between pivot points: 26.5mm
[0148] Radius of the pressure head: 5mm
[0149] Radius of pivot point: 5mm
[0150] Test temperature: 23℃±2℃
[0151] Tables 1 and 2 show the flexural strength and flexural modulus of each sample.
[0152] [Table 1]
[0153]
[0154] [Table 2]
[0155]
[0156] In each electrode of sample No. 1 to No. 17 shown in Table 1, the first oxide constituting the catalyst is formed by an oxide containing Ru and the first element. In No. 1 to No. 13, the first oxide is a composite oxide of Sn, Ru and W. In No. 14, the first oxide is a composite oxide of Sn, Ru and Mo. In No. 15, the first oxide is a composite oxide of Sn, Ru and Ce. In No. 16, the first oxide is a composite oxide of Sn, Ru and Nd. In No. 17, the first oxide is a composite oxide of Sn, Ru and V. The first oxides of these samples do not contain Ir and Pd. Furthermore, the second oxide constituting the intermediate layer of each electrode of sample No. 1 to No. 17 does not contain Ir and Pd. Therefore, each electrode of sample No. 1 to No. 17 can be manufactured at low cost.
[0157] In each electrode of sample No. 101 to No. 118 shown in Table 2, the first oxide constituting the catalyst contains Ru but does not contain the first element. In No. 101 to No. 117, the first oxide constituting the catalyst is composed of an oxide containing at least one of Ir and Pd and Ru. Therefore, the cost of each electrode of sample No. 101 to No. 117 is high. Among these samples, in No. 101 to No. 108, the second oxide constituting the intermediate layer contains at least one of Ir and Pd. Therefore, the cost of each electrode of sample No. 101 to No. 108 is higher. In No. 118, the first oxide is a composite oxide of Sn and Ru.
[0158] The resistivity of each battery of samples No. 1 to No. 17 and the resistivity of each battery of samples No. 101 to No. 118 are all 1.2 Ωcm 2 Since the battery resistivity is low, the battery reactivity of the electrodes of these samples is high to a certain extent. The mass of the catalyst per unit area is 100 g / m 2 No. 1 and No. 14 are compared with No. 101 to No. 117. The cell resistivity of each of No. 1 and No. 14 is equal to or lower than that of each of No. 101 to No. 117. The cell resistivity of each of No. 1, No. 14 to No. 17, which have different compositions of the first oxide constituting the catalyst, is 0.5 Ω cm 2 about.
[0159] In each electrode of Sample No. 1, No. 14 to No. 17, the first oxide constituting the catalyst does not contain Ir and Pd, but has a battery reactivity equal to or higher than that of each electrode of Sample No. 101 to No. 117. This shows that the first oxide containing Ru and the first element has an excellent function as a catalyst.
[0160] In addition, each of the battery resistivity of No. 1 and No. 14 to No. 17 is lower than that of No. 118. Therefore, each of the electrodes of Samples No. 1 and No. 14 to No. 17 has a higher battery reactivity than that of the electrode of Sample No. 118. This shows that the first oxide containing Ru and the first element is composited with the first element, and the function as a catalyst is improved.
[0161] From the results of the cell resistivity of No. 5 to No. 11, it can be seen that even if the mass of the catalyst per unit area is 80 g / m 2 The following can also fully exert the function as a catalyst.
[0162] Comparing samples No. 1 to No. 11, it can be seen that the less the mass of the catalyst per unit area, the higher the mechanical properties of the electrode. The less the amount of catalyst carried on the substrate, the fewer the number of heat treatments in the step of forming the catalyst when manufacturing the electrode. Electrodes with a small mass of catalyst per unit area can suppress the reduction in the mechanical properties of the substrate caused by heat treatment, so it is easy to ensure high mechanical properties. Furthermore, electrodes with a small number of heat treatments have high elasticity and excellent operability, so it can be expected that the yield rate will be improved when assembled in a battery cell.
[0163] Samples No. 9, No. 12 and No. 13 having the same composition of the catalyst and the intermediate layer are compared. The battery resistivity of No. 9 is lower than that of No. 12 and No. 13. The tensile strength of No. 9 satisfies 4.0 MPa or more and 16.0 MPa or less. The tensile modulus of No. 9 satisfies 1.0 GPa or more and 4.0 GPa or less. Furthermore, the bending strength of No. 9 satisfies 3.0 MPa or more and 30.0 MPa or less. The bending modulus of No. 9 satisfies 0.25 GPa or more and 3.0 GPa or less. The tensile strengths and tensile moduli of No. 12 and No. 13 are outside the above range. In addition, the bending modulus of No. 13 is outside the above range. It is therefore believed that electrodes whose mechanical properties are within the specified range are easy to suppress the increase in battery resistivity. Although the electrode having a large amount of catalyst supported on the substrate and having been subjected to a large number of heat treatments has a high bending strength and a high bending modulus, microcracks are likely to occur, and the battery resistivity tends to be high.
[0164] Description of Reference Numerals
[0165] 1: Redox flow battery (RF battery); 7: AC / DC converter; 71: Transformer; 8: Power generation unit; 9: Load; 10: Electrode; 20: Substrate; 21: Particles; 30: Catalyst; 40: Intermediate layer; 100: Battery cell; 101: Diaphragm; 102: Positive electrode cell; 103: Negative electrode cell; 104: Positive electrode; 105: Negative electrode; 106, 107: Tank; 108, 109, 110, 111: Piping; 112, 113: Pump; 120: Battery frame; 121: Bipolar plate; 122: Frame; 127: Sealing member; 200: Battery stack; 210: End plate; 230: Fastening member.
Claims
1. An electrode for a redox flow battery, The electrode comprises a sheet-like substrate and a catalyst supported on the substrate. The substrate is formed of a sintered body in which a plurality of particles containing titanium are bonded to each other. The catalyst includes a first oxide provided so as to cover at least a portion of the plurality of particles. The first oxide is an oxide containing a first element and ruthenium, the first element being at least one selected from the group consisting of tungsten, molybdenum, cerium, neodymium, and vanadium, Each 1m of the electrode 2 The content of iridium and the content of palladium contained in the catalyst are each less than 1 g per area.
2. The electrode according to claim 1, wherein The first oxide includes at least one element selected from the group consisting of tin, antimony, and titanium.
3. The electrode according to claim 1 or 2, wherein An intermediate layer is provided between the particles and the catalyst, The intermediate layer comprises a second oxide, The second oxide is an oxide containing at least one element selected from the group consisting of ruthenium, tin, antimony, titanium, tungsten and molybdenum, The number of kinds of metal elements contained in the second oxide is smaller than the number of kinds of metal elements contained in the first oxide.
4. The electrode according to any one of claims 1 to 3, wherein In the first oxide, the number of moles of ruthenium is greater than the total number of moles of the first elements.
5. The electrode according to any one of claims 1 to 4, wherein The electrode has a porosity of 40 volume % or more and 75 volume % or less.
6. The electrode according to any one of claims 1 to 5, wherein Each 1m of the electrode 2 The content of ruthenium contained in the catalyst is 0.1 g or more and 90.0 g or less in area, Each 1m of the electrode 2 The total content of the first element contained in the catalyst is 0.1 g or more and 50.0 g or less in area.
7. The electrode according to any one of claims 1 to 6, wherein The electrode has a tensile strength of 4.0 MPa or more and 16.0 MPa or less.
8. The electrode according to any one of claims 1 to 7, wherein The electrode has a bending elastic modulus of 0.25 GPa or more and 3.0 GPa or less.
9. A battery cell, which is a battery cell of a redox flow battery having a positive electrode and a negative electrode, wherein: At least one of the positive electrode and the negative electrode is the electrode according to any one of claims 1 to 8.
10. A battery cell, which is a battery cell of a redox flow battery having a positive electrode and a negative electrode, wherein: One of the positive electrode and the negative electrode is the electrode according to any one of claims 1 to 8, The other of the positive electrode and the negative electrode includes a substrate formed of an aggregate of a plurality of carbon fibers. 11 . A redox flow battery comprising the battery cell according to claim 9 or 10 .
